2003
DOI: 10.1093/molbev/msg230
|View full text |Cite
|
Sign up to set email alerts
|

Lineage-Specific Selection in Human mtDNA: Lack of Polymorphisms in a Segment of MTND5 Gene in Haplogroup J

Abstract: Human mitochondrial DNA (mtDNA) is a nonrecombining genome that codes for 13 subunits of the mitochondrial oxidative phosphorylation system, 2 rRNAs, and 22 tRNAs. Mutations have accumulated sequentially in mtDNA lineages that diverged tens of thousands of years ago. The genes in mtDNA are subject to different functional constraints and are therefore expected to evolve at different rates, but the rank order of these rates should be the same in all lineages of a phylogeny. Previous studies have indicated, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 44 publications
0
35
1
Order By: Relevance
“…14,34 Indeed, neutrality tests have revealed lineage-specific differences between the various European mtDNA haplogroups and haplogroup clusters, suggesting that mtDNA has evolved in a lineage-specific manner. 13 We suggest that subhaplogroup J2 and haplogroup K are 'uncoupling genomes.' There are no previous studies on biochemical properties of cells harbouring different mtDNA lineages, but, interestingly, sperm cells harbouring mtDNA haplogroup T have been found to be slower in motility than cells harbouring haplogroup H. 35 …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…14,34 Indeed, neutrality tests have revealed lineage-specific differences between the various European mtDNA haplogroups and haplogroup clusters, suggesting that mtDNA has evolved in a lineage-specific manner. 13 We suggest that subhaplogroup J2 and haplogroup K are 'uncoupling genomes.' There are no previous studies on biochemical properties of cells harbouring different mtDNA lineages, but, interestingly, sperm cells harbouring mtDNA haplogroup T have been found to be slower in motility than cells harbouring haplogroup H. 35 …”
Section: Discussionmentioning
confidence: 92%
“…Endurance runners should have highly efficient ATP production by OXPHOS, whereas sprinters may rely more on anaerobic glycolysis. Despite the crucial role of mitochondrial function in endurance performance, and despite the recent data on lineagespecific differences in mtDNA, 13,14 differences in mtDNA haplogroups between sprinters and endurance runners have not previously been reported. We therefore set out to study mtDNA haplogroup and subhaplogroup frequencies in Finnish track and field athletes competing at the top level in endurance or sprint events.…”
Section: Introductionmentioning
confidence: 94%
“…The association between a combination of these three mtDNA variants and longevity provides the first epidemiological support for the assumption that the pathogenic or adaptive nature of a variant is influenced by interactions with other loci in mtDNA. 19 Our previous study on Finnish nonagenarians has suggested an association between haplogroups J and U and longevity, respectively, and a negative association between haplogroup H and longevity. 11 The absence of 150T in haplogroup H coincides with the lower frequency of this haplogroup among the very old and, similarly, the higher frequency of haplogroup J among the very old coincides with the presence of 150T within haplogroup J2.…”
Section: Discussionmentioning
confidence: 94%
“…Given the paucity of data on the hypervariable region II, and to maximize the number of sequences available for comparative analysis of the mtDNA diversity, the HVII data employed to compute diversity parameters were restricted to the 255 nucleotides encompassed between positions 66 and 320, both inclusive. The reference populations considered in the sequence diversity analyses were Austria, France, Egypt, Spain (Madrid), Spain (Saragossa), US Caucasoids (Budowle et al, 1999), NE Spain (Crespillo et al, 2000), Galicia (Salas et al, 1998(Salas et al, , 2000, Portugal (Pereira et al, 2000), Finland (Moilanen et al, 2003), Balkan (GenBank, accession nos. AY005485-AY005795), Russia (GenBank, accession nos.…”
Section: Discussionmentioning
confidence: 99%